DETERMINAN TINGKAT KEMISKINAN PROVINSI ACEH - Suwanda Ichsan; Said Muhammad (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
AbstractThis study aims to analyze the factors that affect poverty in Aceh Province. Labor ForceParticipation Rate (LFPR), Unemployment Rate, and economic growth are the dominantvariables that affect Aceh’s poverty. The data used in this study is panel data in the period 2008-2015 and analysis model used is multiple linear regression with fixed effect model. The resultsshow that poverty in Aceh Province can be explained by the variables LFPR, unemployment rateand economic growth with R2 of 78.51 percent. The regression coefficient shows that the LFPRvariable has a negative and significant on Aceh's Poverty level, the unemployment rate variablehas a negative and not significant effect on Aceh's poverty level, while the economic growthvariable has a positive and not significant effect on Aceh’s poverty level. The results of thisstudy are expected to be an indicator of the government to choose policies that are suitable forreducing poverty in Aceh Province.Keywords: Poverty, Labor Force Participaton Rate (LFPR), Unemployment, Economic Growth,Fixed Effect Model.